Analysis of Selection of Alternative Materials Outer Support Solar Water Heater - Destri Muliastri; Aldi Alfares; Emsa Ayudia Putri (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
In producing a product, the Manufacturing Industry always prioritizes safety, quality, and profit. One product that prioritizes these criteria is Outer Support on Solar Water Heaters. Currently, the material used in the outer support of the solar water heater is SS 304, the SS 304 material is considered too expensive, so the profits obtained by the manufacturing industry are very small. In addition, SS304 material from year to year is getting harder and harder to find. In this study, an analysis of the selection of alternative outer support materials for solar water heaters was carried out in order to obtain materials that can fulfill the outer support function at a relatively cheap price, do not reduce the outer support function and are easy to obtain or many on the market. The method used in this study uses the Analytical Hierarchy Process (AHP) and CES edupack software as the process of selecting materials. In this study, several tests of mechanical properties were carried out, namely tensile tests, hardness tests, and corrosion resistance tests to determine the mechanical properties of the material, and simulations of selected materials were carried out using Solidworks software, with the aim of knowing the maximum stress value and safety factor. The results obtained from this study obtained an alternative material, namely AISI 201 for the outer support. The results of the hardness test obtained the best hardness value in AISI 201 of 177.17 VHN. The results of the tensile test obtained a yield strength value of 390.35 MPa on AISI 201 material